Transbilayer (flip-flop) lipid motion and lipid scrambling in membranes - Contreras, F. Xabier; Sánchez-Magraner, Lissete; Alonso, Alicia; Goñi, Félix M. (FEBS letters, 2010)
This paper reviews the current knowledge on the various mechanisms for transbilayer, or flip-flop, lipid motion in model and cell membranes, enzyme-assisted lipid transfer by flippases, floppases and scramblases is briefly discussed, while non-catalyzed lipid flip-flop is reviewed in more detail. Transbilayer lipid motion may occur as a result of the insertion of foreign molecules (detergents, lipids, or even proteins) in one of the membrane leaflets. It may also be the result of the enzymatic generation of lipids, e.g. diacylglycerol or ceramide, at one side of the membrane. Transbilayer motion rates decrease in the order diacylglycerol ≫ ceramide ≫ phospholipids. Ceramide, but not diacylglycerol, can induce transbilayer motion of other lipids, and bilayer scrambling. Transbilayer lipid diffusion and bilayer scrambling are defined as two conceptually and mechanistically different processes. The mechanism of scrambling appears to be related to local instabilities caused by the non-lamellar ceramide molecule, or by other molecules that exhibit a relatively slow flip-flop rate, when asymmetrically inserted or generated in one of the monolayers in a cell or model membrane.